VERTICAL DISTRIBUTIONS OF TEMPERATURE, SALINITY AND GEOSTROPHIC FLOW ALONG 175°E IN THE ROSS SEA SECTOR OF THE SOUTHERN OCEAN IN JANUARY 1967 (EXTENDED ABSTRACT) (Twelfth Symposium on Polar Biology) - ナガノブ, ミキオ; NAGANOBU, Mikio (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper